Simulation of crack propagation in prestressed concrete sleepers by fracture mechanics. (February 2019) - Farnam, S.M.; Rezaie, F.
Abstract: Mode I crack propagation in prestressed concrete sleepers B70 is simulated by a fracture mechanics approach. The plastic damage model, which takes the non-linear behavior of concrete into account, is utilized to calculate crack length and crack mouth opening displacement (CMOD). Numerical data from prestressed concrete sleepers B70 under three-point bending load are compared with those of the proposed fracture mechanics model. In this study, fracture mechanics parameters of prestressed concrete sleepers are investigated. Sleepers with the length of initiation crack of 5 to 45 mm (with 10 mm steps) and the width of initiation crack of 2 to 8 mm (with 2 mm steps) are analyzed. Sleeper cracks are created in the notch and both of its sides. These analyses confirm that the structural behavior of prestressed concrete sleepers can be predicted by a simple fracture mechanics model provided that the related material properties like KIC, crack length and CMOD, are known. Highlights: Fracture mechanics of pre-stressed concrete sleeper B70 is studied with numerical analysis. We model B70 sleeper which have 5 crack initiation lengths and 4 crack initiation width in center of sleepers. Force-Crack length and Force-CMOD diagrams are measured for notched sleeper models in center and sides of sleepers and compared together. This paper follows sleeper B70 paper "F. Rezaei, S.M. Farnam, Fracture mechanics analysis of pre-stressed concrete sleepers via investigating crack initiation length, Eng. Fail. Anal, 58 (2015) 267–280".